2022
DOI: 10.3390/ijerph19127446
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Orthodontic Malocclusions in Healthy Children and Adolescents: A Systematic Review

Abstract: The purpose of this study was to systematically review the literature regarding the prevalence of malocclusion and different orthodontic features in children and adolescents. Methods: The digital databases PubMed, Cochrane, Embase, Open Grey, and Web of Science were searched from inception to November 2021. Epidemiological studies, randomized controlled trials, clinical trials, and comparative studies involving subjects ≤ 18 years old and focusing on the prevalence of malocclusion and different orthodontic fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 102 publications
3
19
0
2
Order By: Relevance
“…11,12 Literature acknowledges the importance of an inclusive valuation of orthodontic treatment needs from both an objective and a subjective perspective as being of value to public health authorities, health care providers and patients, especially in terms of their oral health-related quality of life. 13,14 Studies undertaken previously to assess orthodontic treatment need revealed varying rates of agreement between DAI, IOTN-DHC, & IOTN-AC. Kappa coefficient (Cohen's κ) in the range of 0.31-0.55 was found in all the studies, suggesting a mild to moderate agreement between these indices.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Literature acknowledges the importance of an inclusive valuation of orthodontic treatment needs from both an objective and a subjective perspective as being of value to public health authorities, health care providers and patients, especially in terms of their oral health-related quality of life. 13,14 Studies undertaken previously to assess orthodontic treatment need revealed varying rates of agreement between DAI, IOTN-DHC, & IOTN-AC. Kappa coefficient (Cohen's κ) in the range of 0.31-0.55 was found in all the studies, suggesting a mild to moderate agreement between these indices.…”
Section: Discussionmentioning
confidence: 99%
“…Xerostomia involves a high percentage of patients, with a maximum of 71% of findings; this condition can favor the onset of infections of the teeth and gums and create the conditions for an altered dental occlusion [ 15 ]. Malocclusion is defined as an alteration of the relationship between the upper and lower first molars; this condition lays the foundations for the detection of oral infections, becoming a vicious circle [ 16 ]. The same infections can alter the arrangement and presence of the teeth, causing malocclusion [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…Malocclusion is defined as a misalignment or incorrect relation between the teeth of the two dental arches when they approach each other as the jaws close. It ranks third among oral diseases following dental caries and periodontal disease, affecting more than 3.5 billion individuals worldwide, resulting in substantial economic losses globally [8]. The World Dental Federation reports that malocclusion negatively influences oral health, increasing the risk of dental caries, periodontitis, trauma, and 6 These authors contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%